Interdisciplinary Review Of Nursing And Physiotherapy Roles In Patient Rehabilitation (The Review of Diabetic Studies, 2025)
Interdisciplinary collaboration between nursing and physiotherapy has become a fundamental component of contemporary healthcare, particularly in rehabilitation, postoperative management, and chronic disease care. This review examines the complementary roles of nurses and physiotherapists in improving patient outcomes, enhancing functional recovery, and promoting holistic care. Nursing practice emphasizes continuous patient monitoring, medication administration, health education, psychological support, and coordination of care, while physiotherapy focuses on restoring mobility, improving physical function, preventing complications of immobility, and facilitating long-term rehabilitation through evidence-based therapeutic interventions. The integration of these professions is especially critical in intensive care, stroke rehabilitation, orthopedic recovery, and geriatric management, where early mobilization and coordinated treatment strategies significantly reduce hospital stay, disability, and readmission rates. Effective communication, shared care planning, and interdisciplinary training are identified as key factors that strengthen collaborative practice and patient-centered care delivery. However, challenges such as workload pressures, organizational barriers, and unclear professional boundaries may limit optimal teamwork. Strengthening structured collaboration models and institutional support mechanisms is therefore essential. The findings highlight that coordinated nursing and physiotherapy practice plays a vital role in improving safety, functional independence, and quality of life across diverse clinical settings.